2019
DOI: 10.2147/ijn.s211496
|View full text |Cite
|
Sign up to set email alerts
|

<p>Improving <sup>131</sup>I Radioiodine Therapy By Hybrid Polymer-Grafted Gold Nanoparticles</p>

Abstract: Background: Human trials combining external radiotherapy (RT) and metallic nanoparticles are currently underway in cancer patients. For internal RT, in which a radioisotope such as radioiodine is systemically administered into patients, there is also a need for enhancing treatment efficacy, decreasing radiation-induced side effects and overcoming radio-resistance. However, if strategies vectorising radioiodine through nanocarriers have been documented, sensitizing the neoplasm through the use of nanotherapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Le Goas M. et al (2019) improved internal radiotherapy with 131 I by the conjugation of the radioisotope with polymer-grafted AuNPs [71]. The results were promising, with a significant increase in melanoma cell death in vitro and in vivo [71].…”
Section: Radiation Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…Le Goas M. et al (2019) improved internal radiotherapy with 131 I by the conjugation of the radioisotope with polymer-grafted AuNPs [71]. The results were promising, with a significant increase in melanoma cell death in vitro and in vivo [71].…”
Section: Radiation Therapymentioning
confidence: 98%
“…Le Goas M. et al (2019) improved internal radiotherapy with 131 I by the conjugation of the radioisotope with polymer-grafted AuNPs [71]. The results were promising, with a significant increase in melanoma cell death in vitro and in vivo [71]. Daneshvar F. et al (2019) combined X-ray radiotherapy with 808 nm diode laser photothermal therapy of melanoma B16/F10cells after their sensitization with PtNPs [15].…”
Section: Radiation Therapymentioning
confidence: 99%
“…This feature is the object of the in vitro and in vivo studies that will be showed in a forthcoming paper. 30 Overall, the assessed toxicity should be tempered by the conditions used here. Indeed, the incubation time (48 hours) was longer than the average time used elsewhere (see experimental section).…”
Section: B)mentioning
confidence: 99%
“…In a forthcoming paper, more detailed biological effects and particularly, in vitro and in vivo studies will be presented. 30 A covalently grafted polymer corona does not only help to stabilize the nanoparticles (NPs) but it also improves the solubility, the diffusion inside cells, and permits additional effects via the grafting of a therapeutic agent. 31 Here, we synthesized AuNPs with different polymer corona via a "grafting through" or a "direct" process (polymer-AuNPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation